Signal Detection Algorithm Design Based on Stochastic Resonance Technology Under Low Signal-to-Noise Ratio - Jiang, Xiaolin; Diao, Ming; Qu, Susu (Shanghai jiao tong da xue xue bao, 2019)
In the current 4th generation (4G) communication network, the base station with the same frequency transmission makes a serious interference among adjacent cells, and information transmission is susceptible to interference such as channel multipath fading and occlusion effect. Detecting effectively spectrum signal under low signal-to-noise ratio (SNR), directly affects the whole performance of the wireless communication network system. This paper designs an energy signal detection algorithm based on stochastic resonance technology which transforms noise’s signal energy into useful signal energy, and improves output SNR. The energy signal detection algorithm realizes the function of providing effective detection of signal under low SNR, and promotes the performance of the whole communication system.